International GAAP 2020. Vol.1 : generally accepted accounting practice under international financial reporting standards / Jeremy Barnes ... [et al.] - EY International Financial Reporting Group
International GAAP 2020 is a comprehensive guide to interpreting and implementing International Financial Reporting Standards (IFRS), setting IFRS in a relevant business context, and providing insights into how complex practical issues should be resolved in the real world of global financial reporting. This book is an essential tool for anyone applying, auditing, interpreting, regulating, studying, or teaching IFRS. Written by financial reporting professionals from around the world, this guide to reporting under IFRS provides a global perspective, clearly explaining complex technical accounting issues and setting IFRS in a practical context. Numerous worked examples and hundreds of illustrations from the published financial reports of major listed companies from around the world are included. The 2020 edition has been fully revised and updated with information on the latest IFRS changes and current issues.